1999
DOI: 10.1093/ageing/28.3.307
|View full text |Cite
|
Sign up to set email alerts
|

Carer distress in the general population: results from the Sydney Older Persons Study

Abstract: Objective: to assess distress in a sample of carers who were selected from a community survey rather than recruited via community-service agencies. Methods: a community survey was carried out on 630 people aged 75 or over living in Sydney, Australia. Informants nominated by these elderly people were divided into full carer (n = 21), partial carer (n = 187) and noncarer groups (n = 344). Informants completed the General Health Questionnaire (a continuous measure of psychiatric symptoms), the life satisfaction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…FuU carers reported lower life satisfaction than non-carer groups (Broe et al, 1999). This suggests that a greater amount of time spent caregiving is associated with a reduction in life satisfaction.…”
Section: Life Satisfactionmentioning
confidence: 87%
See 1 more Smart Citation
“…FuU carers reported lower life satisfaction than non-carer groups (Broe et al, 1999). This suggests that a greater amount of time spent caregiving is associated with a reduction in life satisfaction.…”
Section: Life Satisfactionmentioning
confidence: 87%
“…Nevertheless, the research evidence on marital cohesion is inconclusive. Some studies of elderly carers have suggested that pre-morbid quaUty of relationship may be an important predictor of stress and emotional health (Broe et al, 1999;Yates et al, 1999;Dunkin and Anderson-Hanley, 1998), On the contraty, others have suggested that better quaUty of relationship may resuh ui greater levels of carer overload (Lawrence et al, 1998).…”
Section: Additional Factorsmentioning
confidence: 99%
“…These carers also experienced higher levels of burden and depression than carers in a younger age bracket. These risk factors are also evident in dementia caregiver of any age group (Broe et al, 1999;Leggett, Zarit, Taylor, & Galvin, 2010;Moon & Dilworth-Anderson, 2014;Pinquart & Sörensen, 2003, 2007Vitaliano, Zhang, & Scanlan, 2003;Wang, Robinson, & Carter-Harris, 2014) and are also likely to be associated with higher levels of burden in a younger caregiver population (Abdollahpour, Nedjat, Noroozian, Salimi, & Majdzadeh, 2014;Adelman, Tmanova, Delgado, Dion, & Mark S. Lachs, 2014;Harwood et al, 2000;Leggett et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Borg and Hallberg (2006) also found that male caregivers had higher life satisfaction than female caregivers. This is consistent with other research findings that male caregivers find caregiving more rewarding (Broe et al, 1999;DiBartolo and Soeken, 2003;Ekwall & Hallberg, 2007). In addition, other researchers found that caregivers with more feelings of isolation and emotional stress also had lower life satisfaction (Matthews, Baker, & Spillers, 2004).…”
Section: Stresssupporting
confidence: 91%
“…Also, research indicates that women are in better physical health and maintained higher levels of socialization outside of caregiving (DiBartolo & Soeken, 2003). However, men were more satisfied with the role of caregiving than women (Broe et al, 1999;DiBartolo & Soeken, 2003;Ekwall & Hallberg, 2007). Ekwall and Hallberg (2007) noted that men were more likely to be experiencing caregiving for the first time compared to women and therefore, experienced more personal growth in the role of family caregiver than women caregivers.…”
Section: Men and Women Caregiversmentioning
confidence: 99%